Number of embryos biopsied as a predictive indicator for the outcome of preimplantation genetic diagnosis by fluorescence in situ hybridisation in translocation cases. Issue 1 (20th January 2015) - Tulay, P.; Gultomruk, M.; Findikli, N.; Bahceci, M.
Summary: This study aimed to investigate the optimum number of embryos to be biopsied in order to increase the likelihood of obtaining a balanced/normal embryo following preimplantation genetic diagnosis (PGD) by fluorescence in situ hybridisation (FISH) for translocation carriers. Patients with low number of fertilised oocytes (≤5) or low number of embryos available for PGD (<7) underwent multiple hormonal stimulation cycles and their embryos from each cycle were vitrified and accumulated to obtain at least three embryos for PGD. Fifty-seven PGD cycles were performed for translocation carriers by FISH on day 3 of embryo development. PGD and pregnancy outcomes were examined according to the number of embryos biopsied. The cancellation rates of embryo transfer for the reciprocal translocation carriers were 40% when more than eight embryos were biopsied and it was as high as 78% when low number of embryos (less than nine) were biopsied. For Robertsonian translocation carriers, when more than eight embryos were biopsied, there were no embryo transfer cancellations. This study showed that when there are more than nine embryos biopsied for PGD, the likelihood of obtaining a balanced embryo and positive pregnancy outcome is significantly higher ( P < 0.05) in such the overall pregnancy rate was 63% for reciprocal and 86% for Robertsonian carriers. This was reduced to only 7% for reciprocal and 14% for Robertsonian translocation carriers when less than nine embryos were biopsied. One of the limitations of this study was that the analysis was performed by FISH and more studies should investigate the outcomes of embryo accumulation following comprehensive chromosome analysis.